Production of Brown Rice Fermented by Ganoderma lucidum - GU Dandan, DONG Xue, ZHANG Jinxiu, LÜ Jianhua, LI Zhuang, QI Yonghao, WANG Li’an (Shipin Kexue)
Brown rice fermented by Ganoderma lucidum (BRFG) was prepared through solid-state fermentation. The fermentation process was optimized by the combined use of single factor experiments and orthogonal array design, and the nutritional components and physicochemical properties of BRFG were analyzed. Additionally, BRFG was used as an ingredient to develop an instant rice porridge product. The results indicated that the optimal preparation conditions for BRFG were determined as follows: solid-to-liquid ratio, 1:0.9 (g/mL); initial pH 7.0; inoculum amount, five blocks; and fermentation for 10 days after the mycelium fully covered the culture medium. In BRFG prepared under these conditions, the crude fiber content was 1.05%, and the relative content of non-starch polysaccharide (NSP) was 9.34%. Compared with brown rice, the protein content of BRFG increased to 10.40%, and the fat content decreased to 2.50%. The content of soluble dietary fiber (SDF) increased to 2.14%, and the content of insoluble dietary fiber (IDF) decreased to 5.51%, with no significant change being observed in the contents of carbohydrates or total dietary fibers (TDF). The surface of BRFG was more wrinkled with numerous small pores, and the shape of starch granules was deformed along with a reduction in starch granules. Furthermore, BRFG demonstrated significant improvement in water-holding capacity, oil-holding capacity, and swelling capacity, as well as enhanced cholesterol adsorption capacity in simulated human gastric and intestinal conditions. Moreover, BRFG exhibited significant increase in scavenging capacity against 1,1-diphenyl-2-picrylhydrazyl (DPPH), hydroxyl and superoxide anion radicals, as well as total antioxidant capacity. The instant rice porridge containing BRFG flour as the primary ingredient had good visual appearance and taste. This study demonstrates that BRFG possess improved nutritional quality and functional characteristics than does brown rice, providing substantial support for its industrial production and multi-scenario application and offering guidance for the development of new functional and nutritional foods.